The Urgency of Updating Auction Law Policy in Indonesia to Improve the Effectiveness of Law Enforcement and the Protection of Community Rights - Soegianto, Soegianto (Universitas Islam Sultan Agung, 2026)
Auction law policy in Indonesia plays a strategic role as a law enforcement instrument, particularly in the execution of court decisions and the settlement of civil obligations. However, in practice, various dynamics and problems still hamper its effective implementation. This study aims to analyze the urgency of reforming auction law policy in Indonesia to improve the effectiveness of law enforcement and strengthen the protection of public rights. The research method used is normative juridical with a statutory and conceptual approach. The results show that the dynamics of auction law policy in Indonesia are characterized by regulatory asymmetry, weak transparency, and the emergence of post-auction disputes that are detrimental to the parties. Furthermore, the development of electronic-based auctions has not been fully supported by a comprehensive legal framework, thus creating potential legal uncertainty. From the perspective of law enforcement effectiveness, reforming auction law policy is a necessity to create a simpler, more transparent, and more accountable system. This reform also needs to be directed at strengthening institutions and optimizing the use of information technology in the auction process. The implications of reforming auction law policy not only impact the effectiveness of law enforcement but also on the protection of public rights more broadly. Adaptive and responsive policies will ensure legal certainty for debtors, creditors, and auction participants, as well as provide access to justice for injured parties. Therefore, updating auction legal policy in Indonesia is a strategic step in realizing a legal system that is just, transparent, and oriented toward protecting public rights.